2022
DOI: 10.3390/rs14102432
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Koalas with Deep Learning Ensembles

Abstract: Effective management of threatened and invasive species requires regular and reliable population estimates. Drones are increasingly utilised by ecologists for this purpose as they are relatively inexpensive. They enable larger areas to be surveyed than traditional methods for many species, particularly cryptic species such as koalas, with less disturbance. The development of robust and accurate methods for species detection is required to effectively use the large volumes of data generated by this survey metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recent technological advances, such as better battery capacity, improved sensors, and lower cost, have accelerated the applications of aerial drones, also known as uncrewed or unmanned aerial vehicles (UAV), unmanned aerial systems (UAS) and remotely piloted aircraft systems (RPAS), in the field of ecology and wildlife monitoring [22][23][24][25][26][27][28][29][30]. Especially multirotor drones, as opposed to fixed-winged drones, equipped with thermal infrared (TIR) cameras have proven to be a useful tool for monitoring cryptic and nocturnal species, on par with spotlight methods [3,25,26,[30][31][32][33][34][35][36][37][38]. In a review, Linchant et al [30] pointed out that several studies have examined the rising potential of the use of drones for wildlife monitoring, but these have primarily been conducted in classic line transects with the sensors pointed directly downwards, so there exists a need to explore and develop new methods.…”
Section: Drones In Wildlife Monitoringmentioning
confidence: 99%
“…Recent technological advances, such as better battery capacity, improved sensors, and lower cost, have accelerated the applications of aerial drones, also known as uncrewed or unmanned aerial vehicles (UAV), unmanned aerial systems (UAS) and remotely piloted aircraft systems (RPAS), in the field of ecology and wildlife monitoring [22][23][24][25][26][27][28][29][30]. Especially multirotor drones, as opposed to fixed-winged drones, equipped with thermal infrared (TIR) cameras have proven to be a useful tool for monitoring cryptic and nocturnal species, on par with spotlight methods [3,25,26,[30][31][32][33][34][35][36][37][38]. In a review, Linchant et al [30] pointed out that several studies have examined the rising potential of the use of drones for wildlife monitoring, but these have primarily been conducted in classic line transects with the sensors pointed directly downwards, so there exists a need to explore and develop new methods.…”
Section: Drones In Wildlife Monitoringmentioning
confidence: 99%
“…Over the past decade, artificial intelligence has led to significant progress in the domain of computer vision, automating image and video analysis tasks. Among computer vision methods, Convolutional Neural Networks (CNNs) are particularly promising for future advances in automating wildlife monitoring [6,[12][13][14][15][16][17][18]. Corcoran et al [3] concluded that when implementing automatic detection, fixed-winged drones with RGB sensors were ideal for detecting larger animals in open terrain, whereas, for small, elusive animals in more complex habitats, multi-rotor systems with infrared (IR) or thermal infrared sensors are the better choice, especially when monitoring cryptic and nocturnal animals.…”
Section: Automatic Detection and Computer Visionmentioning
confidence: 99%
“…A popular and open-source group of CNNs is the YOLO (You Only Look Once) object detection and image segmentation models, with several iterations and active development [14,[19][20][21][22], and a technology cross-fusion with drones has already been proposed as YOLO-Based UAV Technology (YBUT) [6]. The advantages of the YOLO models are that they are fast [8], making it possible to perform object detection in real-time on live footage, and that they are relatively user-friendly and intuitive, making the models approachable to non-computer scientists.…”
Section: You-only-look-once-based Uav Technologymentioning
confidence: 99%
See 1 more Smart Citation